Strategies and Challenges in Interdisciplinary English Language Teaching at the Preschool Level: A Qualitative Analysis - Aprilia, Putri Kurniawan; Romadhon, M. Galuh Elga; Fikri, Dzul; Mustofa, Mutmainnah (Universitas Hamzanwadi, 2023)
This study employs qualitative research methods, particularly narrative inquiry, to explore the challenges preschool teachers face in teaching English to young learners. Through face-to-face semi-structured interviews, a purposively selected and diverse group of four early childhood educators, each with varying English language proficiency and educational backgrounds, provided insights into their experiences. This research primarily investigates the strategies these teachers implement to effectively manage interdisciplinary teaching activities and to enhance student engagement with English language materials. Additionally, it examines into the enduring impacts of these instructional strategies on preschool students, as reported by the teachers. The findings are organized into three key themes: the specific challenges faced in English language instruction, the strategies developed to address these challenges, and the short- to medium-term effects observed by the teachers. These outcomes offer significant implications for educators and policymakers in the realm of early childhood education. They contribute to a deeper understanding of effective teaching practices and inform the development of curricula and pedagogical approaches that can better support English language acquisition among preschoolers.